help, question is below :)))
![help question is below class=](https://us-static.z-dn.net/files/d44/b6e4c18ff1d5648f3da2f421770b4a37.png)
Answer:
2 and 9
Step-by-step explanation:
-4 - (-6) = 2
6 - (-3) = 9
Hope this helps :)
Answer: 2, 9
Step-by-step explanation:
Equation 1
-4 - (-6)
-4+6= 2
This is because whenever you have a number minus a negative number like x - (-y), you cross out the 2 minuses and make them a +. Let's do the same for the 2nd equation:
6-(-3)
As I mentioned, the 2 minuses become a plus, so you just get rid of them. Now, we have 6+3
6+3= 9